Functional effect of the C242T polymorphism in the NAD(P)H oxidase p22phox gene on vascular superoxide production in atherosclerosis. - Guzik, T; West, N; Black, E; McDonald, D; Ratnatunga, C; Pillai, R; Channon, K (2000)
BACKGROUND: Increased superoxide anion production increases oxidative stress and reduces nitric oxide bioactivity in vascular disease states. NAD(P)H oxidase is an important source of superoxide in human blood vessels, and some studies suggest a possible association between polymorphisms in the NAD(P)H oxidase CYBA gene and atherosclerosis; however, no functional data address this hypothesis. We examined the relationships between the CYBA C242T polymorphism and direct measurements of superoxide production in human blood vessels. METHODS AND RESULTS: Vascular NAD(P)H oxidase activity was determined in human saphenous veins obtained from 110 patients with coronary artery disease and identified risk factors. Immunoblotting, reverse-transcription polymerase chain reaction, and DNA sequencing showed that p22phox protein, mRNA, and 242C/T allelic variants are expressed in human blood vessels. Vascular superoxide production, both basal and NADH-stimulated, was highly variable between patients, but the presence of the CYBA 242T allele was associated with significantly reduced vascular NAD(P)H oxidase activity, independent of other clinical risk factors for atherosclerosis. CONCLUSIONS: Association of the CYBA 242T allele with reduced NAD(P)H oxidase activity in human blood vessels suggests that genetic variation in NAD(P)H oxidase components may play a significant role in modulating superoxide production in human atherosclerosis.